The ‘Cod-Multiple’: Modes of Existence of Fish, Science and People - Heike Schwermer; Alexandra M. Blöcker; Christian Möllmann; Martin Döring (Sustainability, 2021)
Fish represent a politically regulated, scientifically researched, industrially processed, commercially marketed and socially contested living marine resource. Related to this, the incorporation of resource users and stakeholders into fisheries management is particularly important. Such involvement has recently improved in terms of frequency, but institutional frameworks often result in a lack of recognition and integration of the diverse ‘knowledges’ of stakeholders involved. Against this background, we aim to uncover the potentials of additional knowledge types for management purposes, paving the way toward a more collaborative management. We first conducted qualitative expert interviews with different stakeholder groups (e.g., commercial fisheries, eNGO and administration) to map various ‘knowledges’ about cod (Gadus morhua), a major resource species in the Western Baltic Sea to reveal the various experiences and epistemologies revolving around it. The second analytical step consisted of examining how these ‘knowledges’ structure, inform and often enter into conflict with perspectives on and assessments of fisheries management. Potentials were identified regarding enhanced stakeholder engagement in management processes that provide food for thought to seek change in sustainable management of fish stocks in the future. Our study is a pointer to the need to transform fisheries management in a more social and participatory way. We argue that sustainable natural resource management cannot be designed solely by integrating more ‘knowledges’ (knowledge sharing) but requires the creation of social contexts and institutions with stakeholder empowerment at the local level (power sharing) to sustainably manage natural resources such as commercially importance fish stocks.